Influence of pollination on canola seed production in the Cerrado of Uberlândia, Minas Gerais State, Brazil - Leandro Fuzaro; Nayara Luchini Xavier; Fábio Janoni Carvalho; Flávia Andrea Nery Nery; Stephan Malfitano Carvalho; Vanessa Andaló (Acta Scientiarum. Agronomy, 2018)
The objective of this study was to evaluate the influence of pollinating insects on canola productivity for different commercial hybrids, Hyola 61 and Hyola 433, in Minas Gerais State, Brazil. The studies were conducted at the Fazenda Experimental Água Limpa of the Federal University of Uberlândia. To evaluate the influence of pollination by bees on the production of canola seeds, an experiment was carried out to exclude floral visitors and compare canola seed production following four treatments: (a) autogamy in Hyola 61, (b) autogamy in Hyola 433, (c) open pollination in Hyola 61, with insects having free access, and (d) open pollination in Hyola 433, with insects having free access. Flowers that were available for pollination had 25% and 18.8% heavier pods and 22.5% and 20.6% more seeds per pod in Hyola 61 and Hyola 433, respectively, than those bagged without pollination. The results show that the cross-pollination process, fostered by pollinator visits, positively influenced some parameters related to production, presenting an advantage in relation to canola autogamy in Cerrado Mineiro.